The Prognostic Role of In-Hospital Mortality Predictors and De Ritis Ratio in Patients with Upper Gastrointestinal System Bleeding - Ayşenur Uçar, Aynur Doğrusöz (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: We aimed to evaluate the prognostic significance of the aspartate aminotransferase(AST) / alanine aminotransferase (ALT) named as (De Ritis) ratio in patients hospitalized in the intensive care unit with the diagnosis of upper gastrointestinal (GI) bleeding. Method: We retrospectivelyanalyzed the clinical and laboratory data of 243 patients admitted with upper GI bleeding to the intensive care unit of our tertiary hospital between January 2018 and April 2022. The potential prognostic parameters between survivors and non-survivors groups and then between low De Ritis and High De Ritis groups were compared. The effect of the De Ritis ratio on in-hospital mortality was investigated by logistic regression analysis. Results: Of the two hundred andforty-three patients hospitalized with upper GI bleeding, 65.8% were male. The mean age of the patients was 68.6±11.56. The cut-off value for low and high De Ritis groups was selected as 1.57,which value seperated second tertile and third tertile of the patient population.İn hospital mortality rate was 13.1%. While albumin level was higher in the low De Ritis group, ALT, AST, and INR values ​​were higher in the high De Ritis group. No statistically significant correlation was found between these two groups in terms of mortality. Moreover, De Ritis ratio did not show a significant difference between survivors and non-survivors (p=0.058). Conclusion: It was concluded that the rate of De Ritis is not an independent predictive factor for mortality in patients with upper GI bleeding. But, more prospective and randomized studies are needed to evaluate clearly the prognostic value of the De Ritis ratio in upper GI bleeding patients.Keywords: De Ritis ratio, aspartate aminotransaminase, alanineaminotransaminase, upper gastrointestinal bleeding, mortality